Unexpected Histological Finding of Diffuse Large B-Cell Lymphoma in a Patient with Long-standing Goiter and Hashimoto's Thyroiditis: A Case Report - Dhinar Kemas Ariawidjaja; Mohammad Robikhul Ikhsan; Hemi Sinorita; Raden Bowo Pramono; Vina Yanti Susanti; Rayhani Erika Putri (PP PERKENI, 2025)
Primary thyroid lymphoma (PTL) is an uncommon malignancy, comprising less than 5% of all thyroid cancers. Hashimoto's thyroiditis (HT) is the most significant risk factor, increasing the risk of developing PTL by 40 to 80 times. Diffuse large B-cell lymphoma (DLBCL) is the most prevalent and aggressive histological subtype, accounting for over 50% of PTL cases. The diagnosis is challenging, as the clinical and sonographic features of PTL can mimic benign thyroiditis. A 60-year-old female with a three-year history of a progressively enlarging goiter and worsening compressive symptoms presented for surgical evaluation. Initial investigations revealed severe hypothyroidism and ultrasound findings of a nodular goiter with features of thyroiditis (TI-RADS 3). She underwent a total thyroidectomy for symptomatic relief. Postoperative histopathology unexpectedly revealed a DLBCL, confirmed by CD20 positivity, coexisting with a background of classic HT. The patient was subsequently treated with six cycles of R-CHOP (Rituximab, Cyclophosphamide, Doxorubicin, Vincristine, and Prednisone) chemoimmunotherapy and achieved a complete clinical and radiological response. This case underscores the diagnostic challenge PTL presents, particularly in patients with preexisting HT. A high index of suspicion is crucial for clinicians managing HT patients who present with a rapidly enlarging goiter or worsening compressive symptoms. While fine-needle aspiration has limitations, definitive diagnosis often requires a core needle or excisional biopsy to differentiate neoplastic infiltration from the benign lymphocytic infiltrate of HT.